Food Science - Potter, Norman N.; Hotchkiss, Joseph H. (Food science text series., 1998)
Now in its fifth edition, Food Science remains the most popular and reliable text for introductory courses in food science and technology. This new edition retains the basic format and pedagogical features of previous editions and provides an up-to-date foundation upon which more advanced and specialized knowledge can be built. This essential volume introduces and surveys the broad and complex interrelationships among food ingredients, processing, packaging, distribution and storage, and explores how these factors influence food quality and safety. Reflecting recent advances and emerging technologies in the area, this new edition includes updated commodity and ingredient chapters to emphasize the growing importance of analogs, macro-substitutions, fat fiber and sugar substitutes and replacement products, especially as they affect new product development and increasing concerns for a healthier diet. Revised processing chapters include changing attitudes toward food irradiation, greater use of microwave cooking and microwaveable products, controlled and modified atmosphere packaging and expanding technologies such a extrusion cooking, ohmic heating and supercritical fluid extraction, new information that addresses concerns about the responsible management of food technology, considering environmental, social and economic consequences, as well as the increasing globalization of the food industry. Discussions of food safety an consumer protection including newer phychrotropic pathogens; HAACP techniques for product safety and quality; new information on food additives; pesticides and hormones; and the latest information on nutrition labeling and food regulation. An outstanding text for students with little or no previous instruction in food science and technology, Food Science is also a valuable reference for professionals in food processing, as well as for those working in fields that service, regulate or otherwise interface with the food industry.